Concepts and Concept Formation: Goffman and Beyond - Scheff, Thomas J. (Qualitative Sociology Review, 2006)
The social and behavioral sciences need distinctive concepts to escape entrapment in cultural assumptions. Currently there are several sources for concepts, but vernacular words are most frequently used. These words are usually ambiguous and may reaffirm the status quo. This essay proposes that a new approach is implied in Goffman’s work. Most of the new terms he invented went undefined. However, he can be seen as struggling in much of his writing to develop two basic components of the “looking-glass self,” awareness structures and embarrassment. His method seems to have involved using many vernacular cognates and close examination of detailed examples of each concept. The implication is that it might be possible to ground concepts by 1. Listing and examining links to vernacular and technical cognates, and 2. Closely exploring many concrete examples. A study of one type of awareness structure, collective denial (Zerubavel 2006), can also be used to illustrate the potential of this method.